2022
DOI: 10.1093/jxb/erac393
|View full text |Cite
|
Sign up to set email alerts
|

Using genomic prediction with crop growth models enables the prediction of associated traits in wheat

Abstract: Crop growth models (CGM) can predict the performance of a cultivar in untested environments by sampling genotype-specific parameters (GSPs). As they cannot predict the performance of new cultivars, it has been proposed to integrate CGMs with whole genome prediction (WGP) to combine the benefits of both models. Here, we used a CGM-WGP model to predict the performance of new wheat genotypes that do not have phenotypic records in the reference population. The CGM was designed to predict phenology, nitrogen, and b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 58 publications
0
7
0
Order By: Relevance
“…Future studies should investigate the effect of predicted phenology traits on the prediction accuracy of untested environments. Alternatively, untested or future climates can be predicted in a more straightforward CGM-WGP, which integrates crop growth models and genomic prediction [196].…”
Section: Genomic Selectionmentioning
confidence: 99%
“…Future studies should investigate the effect of predicted phenology traits on the prediction accuracy of untested environments. Alternatively, untested or future climates can be predicted in a more straightforward CGM-WGP, which integrates crop growth models and genomic prediction [196].…”
Section: Genomic Selectionmentioning
confidence: 99%
“…However, we use it in a fundamentally different way as we utilize the historic yield from hybrids that are not necessarily related to the target hybrids to characterize each environment. ECs are another type of data utilized in our model that is becoming more common in GP models (Bustos-Korts et al 2019; Onogi 2022; Jighly et al 2022). Our results confirmed that ECs such as the ones derived from the APSIM crop model are useful features in improving prediction abilities.…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, this study assessed management practices to leverage the performance of sorghum hybrids ( Figure 5B ), envirotyped the target population of environments with distinctive water stress patterns ( Figures 5A, B ), and quantified the impact of the LT trait in the production sorghum area. Crop model applications to support breeding exist for different crops and diverse geographies ( Technow et al., 2015 ; Chenu et al., 2017 ; Hammer et al., 2019b ; Jighly et al., 2023 ). For instance, a study deployed a rice crop model to hypothesize the lack of effectiveness in breeding drought-tolerant upland rice in Brazil ( Heinemann et al., 2019 ), and other studies improved phenomic prediction by integrating crop models and genomic prediction ( Cooper et al., 2002 ; Heslot et al., 2014 ; Crossa et al., 2022 ).…”
Section: Discussionmentioning
confidence: 99%